Nicomaco a processo (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2019)
This paper gives a comprehensive reconstruction of the trial that Nikomachos, one of the officials in charge of the revision and republication of laws that took place in Athens between the end of the V and the beginning of the IV century, underwent at the end of the year 399/8 BC. Starting from the analysis of Lysias’ Against Nikomachos, the only source on this judicial case, the paper consists of two parts. The first section, next to the analysis of rhetorical features of Lysianic text, discusses the procedural details of Nikomachos’ trial and argues that it arose from the accounting at the end of his term of office. The second section focuses both on the kind of the task performed by Nikomachos and on his charge. The comparison among Lysias’ speech and other epigraphic and literary data, with special attention to the Teisamenos’ decree preserved by Andocides’ On the Mysteries, provides for the hypothesis that Nikomachos was brought on trial on charge of damage to the city’s estate because of alleged failures in the laws’ transcription that he carried out not as anagrapheus, but as nomothetes.